A methodology for designing class-F−1/J(J−1) high efficiency concurrent dual-band power amplifier. (November 2018) - Shariatifar, Milad; Jalali, Mohsen; Abdipour, Abdolali
Abstract: This paper, presents a methodology for designing concurrent dual-band power amplifier (DB-PA) that operates in Class-F −1 at one band and Class-J or Class-J −1 at the other band. It is shown that the second harmonic engineering of Class-F −1 and Class-J or Class-J −1 makes these classes of operation compatible in terms of dual-band realization without introducing higher complexity in realizing the harmonic control network. The design methodology is well illustrated and is validated by implementing a Class F −1 /J concurrent dual-band PA operating at 1842 and 2655 MHz bands. Experimental results exhibit output powers of 40 and 41 dBm and efficiencies of 76% and 70% at the lower and upper bands, respectively. The AM-AM, AM-PM and two-tone third-order inter-modulation distortion results imply a good linearity behaviour of the designed PA. Furthermore, the linearity of the designed DB-PA is also verified with a single carrier WCDMA signal, where the PA shows better than −20 dBc adjacent channel power ratio in saturation region at both of the operating bands.